ANALISIS KUALITAS PELAYANAN WISATA SEJARAH KOMPLEK MASJID BANTEN LAMA-BENTENG SUROSOWAN DITINJAU DARI KARAKTERISTIK PENGUNGJUNG DALAM IMPLEMENTASI KEBIJAKAN PARIWISATA - Sonny Sonny (Jurnal Renaissance, 2016)
Tourism policy implementation Mosque Complex History of Banten Lama - Benteng Surosowan. Business and visitors Mosque Complex History of Banten Lama - Benteng Surosowan consist of various heterogeneous characteristics, it can bring up the problems of the quality level of service to visitors, the Service Quality History Analysis of Complex Mosque of Banten Lama - Benteng Surosowan Seen From Visitor Characteristics In Implementation Tourism Policy. This research was conducted at the site of Masjid Complex History of Banten Lama - Benteng Surosowan, by taking samples at the visitors, with a technique that is used is " accidental saturated " with a sample of 100 visitors. Results of studies using analysis tools that test instruments , Normality Test Data, Test Data and Test Homogeneity difference with the hypothesis, the results of studies that show a visitor perception Mosque Complex History of Banten Lama - Benteng Surosowan Seen From Visitor Characteristics In Tourism Policy Implementation , there is a difference significant , difference Level Service Quality History of Banten Lama Mosque complex - Benteng Surosowan Seen From the visitor characteristics that occupational factors, gender , age , and education. Achievement level of visitor satisfaction obtained results approaching the maximum satisfaction level of 83 % is obtained figures from the maximum satisfaction level of 100 %. In addition to the above conclusion of the study is that there is a significant difference in the perception of the presence of visitors with a tendency Employees Employees with Organizational Characteristics that visitors who worked as in private , visitors are female, aged 17 to 25 years, educated visitors S2/S3 tend to feel more satisfied.Key Words: Service quality, satisfied